2000
DOI: 10.1002/(sici)1096-8628(20000320)91:3<227::aid-ajmg14>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube defects and the 13q deletion syndrome: Evidence for a critical region in 13q33-34

Abstract: Neural tube defects (NTD) are common findings in the 13q deletion syndrome, but the relationship between the 13q- syndrome and NTDs is poorly understood. We present a child with a 13q deletion and lumbosacral myelomeningocele. This was a boy with microcephaly, telecanthus, minor facial anomalies, and ambiguous genitalia. Cytogenetic and fluorescence in situ hybridization analysis showed a de novo 46,XY,del(13)(q33.2-->qter) with no visible translocation. By using microsatellite markers, the deletion breakpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 20 publications
4
25
0
1
Order By: Relevance
“…We showed a strong association with anencephaly for 13q22-q34 (P < 0.0001). Brown et al (1993) deWned a critical region in 13q32; however, Luo et al (2000) questioned this Wnding and suggested deletion in 13q33-q34 as suYcient to cause an NTD. ZIC2 and ZIC5 are considered strong candidate genes for neural tube defects.…”
Section: Discussionmentioning
confidence: 58%
“…We showed a strong association with anencephaly for 13q22-q34 (P < 0.0001). Brown et al (1993) deWned a critical region in 13q32; however, Luo et al (2000) questioned this Wnding and suggested deletion in 13q33-q34 as suYcient to cause an NTD. ZIC2 and ZIC5 are considered strong candidate genes for neural tube defects.…”
Section: Discussionmentioning
confidence: 58%
“…Polymorphisms in these genes, however, are not significantly associated with NTDs in all populations, suggesting that polygenic and environmental factors are important. Our groups and others have described NTDs in chromosomal and inherited syndromes, including trisomy 13 (13)(14)(15)(16), trisomy 18 (16 -19), trisomy 21, and 22q11.2 and 13q deletion syndromes (20)(21)(22)(23). In rare cases, syndromes that variably present with NTDs have been associated with a mutation in a single gene (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…During mouse embryogenesis, high levels of Glypican 5 are expressed in the neural tube (72). Consistent with a potential role of glypicans in spina bifida, patients with 13q deletions that sometimes remove GPC5 and GPC6 can present with NTDs (23,73). Collectively, these results implicate the glypican gene family in promoting normal neural tube development.…”
Section: Introductionmentioning
confidence: 99%
“…We next extended our CGHa analysis to patients who had been reported as having 13q-syndrome which involves various partial deletions in the q22-qter region (Luo et al, 2000;Gutierrez et al, 2001;Hewson and Carter, 2002). These patients have a well-defined set of clinical phenotypes, including mental retardation, where the deletion was generally assumed to involve the terminal region of 13q, although somatic cell hybrid studies (Hawthorn and Cowell, 1995) suggested that these were, in fact, subterminal deletions.…”
Section: Resultsmentioning
confidence: 99%